Numerical simulation of vertical tunneling transistor with bilayer graphene as source and drain regions. Issue 10 (28th June 2017) - Horri, Ashkan; Faez, Rahim; Darvish, Ghafar
Abstract : In this paper, the electrical characteristics of vertical tunneling bilayer graphene field effect transistor (VTBGFET) are theoretically investigated. We evaluate the device behavior using nonequilibrium Green's function (NEGF) formalism combined with an atomistic tight binding model. By using this method, we extract the most significant figures of merit such as ON/OFF current ratio, subthreshold swing, and intrinsic gate‐delay time. The results indicate that using a bilayer graphene instead of a monolayer graphene as the base material for the source and drain regions leads to a larger ON/OFF current ratio due to the presence of an energy bandgap in biased bilayer graphene. Also, the subthreshold swing of VTBGFET can be much lower than that of vertical tunneling monolayer graphene field‐effect transistor (VTMGFET). We find that the increase of the number of hBN layers enhances the ON/OFF current ratio but degrades the intrinsic gate‐delay time.